2014
DOI: 10.4236/ojas.2014.45027
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Close-Up Starting Programs on Performance of Light-Weight Feedlot Steers Calves during the Early Receiving Period

Abstract: The influence of close-up feed strategies on growth performance and dietary NE in light-weight feedlot steers during a 56 d receiving period was evaluated. Dietary treatments were formulated to meet the average metabolizable amino acid requirements of calves during 1) the initial 7 d; 2) the initial 14 d; and 3) the initial 21 d following arrival into the feedlot, assuming average interval DMI of 2.8, 3.0, and 3.6 kg/d, respectively. Thereafter, all steers received dietary treatment 3. Fish meal was the source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…DM intake was 4.91, 5.40 and 5.58 kg/day in group 1, 2 and 3, respectively. Average daily gain of chromium supplemented group during present study were in agreement with Barajas et al (2005), who also reported the higher body weight in calves supplemented with chromium. The increase of body weight gain in these calves could be attributed to the increase in dry matter intake (Kraidees et al 2009).…”
Section: Dry Matter Intake Average Daily Gain and Water Intakesupporting
confidence: 91%
“…DM intake was 4.91, 5.40 and 5.58 kg/day in group 1, 2 and 3, respectively. Average daily gain of chromium supplemented group during present study were in agreement with Barajas et al (2005), who also reported the higher body weight in calves supplemented with chromium. The increase of body weight gain in these calves could be attributed to the increase in dry matter intake (Kraidees et al 2009).…”
Section: Dry Matter Intake Average Daily Gain and Water Intakesupporting
confidence: 91%